Extraction of beta-carotene from the microalga Dunaliella salina using bacterial lipase enzyme and organic solvent under varying stress conditions - Sayegh, Fotoon; Al-naghrani, Mona J.; Amran, Ramzi H.; Jamal, Mamdoh T.; Nass, Nada M.; Felemban, Wessam F.; Jastaniah, Samyah D.; Satheesh, Sathianeson (Frontiers in Marine Science, 2025)
Nowadays there is a growing trend towards carotenoids obtained from natural sources such as microalgae. Dunaliella salina is among the most significant natural sources of beta-carotene for commercial scale, which is used in many food industries. Enzymatic extraction of beta-carotene is one of the safe methods that ensure that the food product is not contaminated compared to ex-traction using solvents. In this study, beta-carotene was extracted using two methods: the organic solvent method by tetrahydrofuran and the enzymatic extraction using a bacterial lipase enzyme. The alga was exposed to different stress conditions (salinity/nitrogen) for increasing the beta-carotene production. The highest value of beta-carotene content was recorded in the extraction method using tetrahydrofuran (109.008 µg/mL at 2.5M NaCl/0.5 g/L KNO3), compared to the extraction method using lipase enzyme (19.13 µg/mL at 1 mg/mL at 24 h exposure time). However, the beta-carotene yield slightly increased (21.4 µg/mL) in lipase enzyme extraction method for the algal samples exposed to more than 24 h under different conditions (3M NaCl/1g/L KNO3). The results show that the enzymatic extraction method is less efficient in extracting beta-carotene compared to the tetrahydrofuran solvent extraction method, with the latter showing a higher content of extracted beta-carotene.